Association of pain management and positive expectations with psychological distress and spiritual well‑being among terminally ill cancer patients admitted to a palliative care unit - Yilong Yang; Meng Cui; Xinxin Zhao; Simeng Wang; Yumei Wang; Xiaohe Wang (BMC, 2023)
Abstract Background Although palliation of psycho-spiritual distress is of great importance in terminally ill cancer patients, there is a little information about screening patients who benefit from palliative care and identifying the cancer care targets. This study explored the relationship of pain management and positive expectations with depression, anxiety and spiritual well-being (SWB) in terminal cancer patients admitted to a palliative care unit. Methods Eighty-four terminal cancer inpatients were recruited from the Hospice Ward, Shengjing Hospital of China Medical University. Optimism and general self-efficacy (GSE) were evaluated at admission. Patients completed self-report questionnaires on SWB, depression, anxiety and pain both on admission and one week later. The repeated designed analysis of variance was used to explore the correlates of depression, anxiety and SWB (meaning, peace, faith). Results In our sample, only cancer pain diminished significantly one week later. For depression (p = 0.041) and faith (p = 0.013), there was a significant pain group (relieved vs. not relieved) × time interaction effect, such that those with satisfied pain control experienced the improved psycho-spiritual outcomes at 1 week. The relationship between positive expectations, peace and faith was also statistically significant, indicating that the improvement of peace or faith was significant in the low group of optimism and GSE. Conclusions Our findings indicated that pain management lied at the center of depression and SWB, meaning that effective pain management may reduce depression, and improve SWB among terminal cancer patients. Moreover, positive expectations, especially for optimism, may be the new target for SWB-related intervention research. Palliative care nurse should require the identification of terminal cancer patients who may more benefit from short-term palliative care, and target them with effective cancer care.